Direct‐Patterning SWCNTs Using Dip Pen Nanolithography for SWCNT/Silicon Solar Cells. Issue 16 (25th March 2018) - Corletto, Alexander; Yu, LePing; Shearer, Cameron J.; Gibson, Christopher T.; Shapter, Joseph G.
Abstract: Dip pen nanolithography (DPN) is used to pattern single‐walled carbon nanotube (SWCNT) lines between the n‐type Si and SWCNT film in SWCNT/Si solar cells. The SWCNT ink composition, loading, and DPN pretreatment are optimized to improve patterning. This improved DPN technique is then used to successfully pattern >1 mm long SWCNT lines consistently. This is a 20‐fold increase in the previously reported direct‐patterning of SWCNT lines using the DPN technique, and demonstrates the scalability of the technique to pattern larger areas. The degree of the uniformity of SWCNTs in these lines is further characterized by Raman spectroscopy and scanning electron microscopy. The patterned SWCNT lines are used as thin conductive pathways in SWCNT/Si solar cells, similar to front contact electrodes. The critical parameters of these solar cells are measured and compared to control cells without SWCNT lines. The addition of SWCNT lines increases power conversion efficiency by 40% (relative). Importantly, the SWCNT lines reduce average series resistance by 44%, and consequently increase average fill factor by 24%. Abstract : Using dip pen nanolithography, 1 mm long lines containing carbon nanotubes (CNTs) are written on Si substrates and improve the performance of single‐walled carbon nanotube/Si heterojunction solar cells. The lines improve the diode properties and lead to an increase in performance of about 40% due to the increased conductivity from the high density of CNTs in the written lines.